MOSAIK: An Agent-Based Decentralized Control System with Stigmergy for a Transportation Scenario - Schmid, Sebastian Josef; Schraudner, Daniel; Harth, Andreas (2023)
We investigate possibilities for implementing the decentralized control of transporters with Semantic Web agents to fulfill a given transportation task. We present the MOSAIK framework as a system to build and simulate agents to control transporters using stigmergy for communication, and self-organize based on local decisions. Our framework uses Semantic Web technologies because the communication paradigm of stigmergy directly maps to the REST constraints of the application architecture of the web. The system achieves self-organization by implementing a combination of simple reflex web agents that coordinate using web resources as environment for stigmergy. Finally, we evaluate our system compared to an agent-based simulation and discuss requirements of decentralized systems on the Semantic Web using stigmergy.<br